STRATEGIC GOVERNANCE, LEADERSHIP INTEGRITY, AND STAKEHOLDER ENGAGEMENT IN RESPONSIBLE AI ADOPTION IN SECURITY SERVICE INDUSTRY - Hotasi Albin Sumitro; Achmad Fajar Hendarman (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The security service industry is increasingly adopting Artificial Intelligence (AI) to enhance surveillance accuracy, operational efficiency, and decision-making processes. Despite its benefits, AI adoption in this sector raises significant concerns related to ethical responsibility, governance, and stakeholder trust. This study examines the role of strategic governance, leadership integrity, and stakeholder engagement in shaping responsible AI adoption within the security service industry.A quantitative research approach was employed using survey data collected from employees across different managerial levels and functional units within a security service organization. The data were analyzed using multiple linear regression after meeting validity, reliability, and classical assumption requirements. The results indicate that strategic governance, leadership integrity, and stakeholder engagement each have a positive and statistically significant effect on responsible AI adoption. Leadership integrity emerges as the most influential factor, highlighting the importance of ethical leadership behavior in guiding responsible technology use.